Differential response of fragrant rice cultivars to salinity and hydrogen rich water in relation to growth and antioxidative defense mechanisms. Issue 11 (19th September 2021) - Fu, Xiaomeng; Ma, Lin; Gui, Runfei; Ashraf, Umair; Li, Yuzhan; Yang, Xiaojuan; Zhang, Jianwen; Imran, Muhammad; Tang, Xiangru; Tian, Hua; Mo, Zhaowen
Abstract: Salinity negatively effects the growth and productivity of crop plants; however, the effects of hydrogen rich water (HRW) on the early growth of fragrant rice under salinity stress are rarely investigated. In present study, two HRW treatments: foliar application (F-HRW) and irrigation (I-HRW) were applied on the two fragrant rice cultivars, Yuxiangyouzhan and Xiangyaxiangzhan, grown under normal and salt stress conditions, i.e., 0 and 150 mmol NaCl L −1, respectively. Plants without HRW application were grown as control (CK). Results showed that the dry weight per unit plant height (mg cm −1 ) was increased by 12.6% and 23.0% in F-HRW and I-HRW, respectively under salt stress as compared with CK. Application of HRW, regardless of the application method, modulated the antioxidant activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) while reduced malondialdehyde (MDA) contents under salt stress. Moreover, significant and positive relations were observed among total dry weight and shoot dry weight, dry weight per unit plant height, SOD and CAT activity in root. Overall, F-HRW application modulated the early growth and related physiological attributes in fragrant rice under salt stress whereas I-HRW was found to mitigate salt stress. Novelty statement : Involvement of endogenous H2 in plants for regulating various physiological functions is of great importance to stimulate and/or activate the antioxidant defense responses against oxidative stress; however, there is a lack of research in this aspect. The present study investigated the effects of hydrogen rich water (HRW) on the growth and physiological attributes of two fragrant rice cultivars grown under salt-stress. It was noteworthy to find that application of HRW either foliar application or irrigation improved the morphological characters, i.e., dry weight per unit plant height and enhanced the activities of antioxidants, i.e., peroxidase, superoxide dismutase and catalase whilst decreased the malonaldehyde content. Overall, the application of HRW modulates plant growth and physiological attributes in fragrant rice cultivars under salt-stress conditions. This study will be helpful in improving the early growth and/or stand establishment of fragrant rice nursery under saline conditions.